some noun paradigms - Elsy Margareta Rankvist; Joshua Karl Wilbur (Joshua Wilbur, 2009)
Linguistic documentation of the Pite Saami language (ISO693-3: sje) noun paradigms for: sabek (ski), guolle (fisk), vuästa (cheese), skåvvlå (school), bärrgo (meat); also short discussion of (near) minimal pairs guolle/guolla and bärrgo/bärrgal. The numbers (in Swedish) refer to the following cases/derivation: 1. NOM.SG; 2. NOM.PL; 3. GEN.SG; 4. GEN.PL; 5. ACC.SG; 6. ACC.PL; 7. ILL.SG; 8.ILL.PL; 9. INESS.SG; 10. INESS.PL; 11. ELAT.SG; 12. ELAT.PL; 13. COM.SG; 14. COM.PL; 15. ABESS.SG; 16. ABESS.PL; 17. ESS; 18. DIM.NOM.SG; 19. DIM.NOM.PL